Evaluation of obstructive sleep apnea in patients with metabolic syndrome - Tien, Hoang Anh; Luong, Tran Nguyen Hien; Hang, Pham Thi Minh; Giang, Nguyen Thi Tra; Uyen, Truong Thi Thu; Duyen, Nguyen Hong; Thang, Doan Chi (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Background: Obstructive sleep apnea syndrome (OSAS) is a common sleep breathing disorder that negatively affects health and quality of life. Assessing the relationship between sleep apnea syndrome and metabolic syndrome promises to bring new approaches, early screening, and appropriate prognosis to groups of patients with high-risk factors. This study aims to investigate the clinical and paraclinical characteristics of Obstructive Sleep Apnea Syndrome in patients with Metabolic Syndrome and to examine the correlation between the Apnea-Hypopnea Index (AHI) and lipid profile indices, blood sugar, waist circumference, blood pressure, and body mass index (BMI). Methods: A cross-sectional descriptive study was conducted by interviewing 36 people aged 18 years and older who were diagnosed with metabolic syndrome according to criteria based on the consensus statement of IDF (international diabetes federation), AHA (American Heart Association)/NHLBI (Association (AHA) /National), WHF (World Federation of Hemophilia), IAS (International Antiviral), and IASO (Indian Association of Surgical Oncolog) in 2009 at the Department of Cardiology and the Department of General Internal Medicine, Hue University of Medicine and Pharmacy Hospital from February 2023 to December 2023. Results: Among 36 patients with metabolic syndrome, 30 had OSAS (83.3%), with mild severity accounting for the majority (52.8%). The mean age of the group with OSAS was 64.1 ± 13.4 years. The BMI and Epworth scores were significantly higher in the OSAS group. Symptoms of snoring, morning headaches, decreased alertness, and memory concentration were significantly higher in the OSAS group. Conclusion: Metabolic syndrome and obstructive sleep apnea syndrome are associated with many factors. Metabolic syndrome has the risk of worsening sleep apnea and vice versa.